Association of Extracellular Signal-Regulated Kinase Genes With Myopia: A Longitudinal Study of Chinese Children - Xiao, Haishao; Lin, Shudan; Jiang, Dandan; Lin, Yaoyao; Liu, Linjie; Zhang, Qiqi; He, Juan; Chen, Yanyan (Frontiers in Genetics, 2021)
Objective The present study was designed to investigate whether the extracellular signal-regulated kinase(ERK) signaling pathway, a downstream component of dopamine signaling, is involved in myopia among Chinese children. Methods During a 3.5-year follow-up period, 488 primary school students were enrolled in this study. The noncycloplegic spherical equivalent refraction(SER) and other ocular parameters were assessed. Four variants of four genes in the ERK signaling pathway were selected, namely, RASGRF1 rs6495367, PTPN5 rs1550870, PTPRR rs11178469 and PDGFRA rs6554163. SNPscan was used to genotype single-nucleotide polymorphisms(SNPs). PLINK software was used to assess the associations of the genetic variants with the occurrence or development of myopia, the SER, and the other ocular parameters. We created a protein-protein interaction(PPI) network and microRNA(miRNA)-gene network using String and Cytoscape. String was also used to conduct enrichment analyses for the genes in these networks. Results In total, 426 children(baseline age: 7.28±0.26 years), including 236(55.4%) boys and 290 girls, were included in the analyses. After adjustment for confounding factors with 10,000 permutations, children with the CT or TT genotype of rs1550870 were found to be more susceptible to myopia than those with the CC genotype(adjusted p= 0.021). Additionally, rs1550870 was correlated with a significant myopic shift and increasing lens thickness(LT) but had a negative effect on central corneal thickness(CCT). Rs 6495367 was negatively associated with myopic shift(additive: p=0.029; dominant: p=0.019) as well as the myopic spherical equivalent(SE) and axial length(AL). In a model, the combination of rs6495367, rs1550870 and rs6554163 was associated with a change in SE(cross-validation consistency[CVC]=5/10, p=0.0107). The genes of the PPI and miRNA-gene interaction networks were submitted to enrichment analyses, which suggested that these genes were mainly involved in eye development and dopaminergic synapse-related processes. Conclusion We identified genetic variants of crucial genes in the ERK signaling pathway that were significantly correlated with myopia and ocular parameter alterations in Chinese children. A combination of gene and miRNA functional analyses with enrichment analyses was used to highlight the regulatory effects associated with ocular development and dopamine biological functions. In summary, this study offers novel clues to understand the role of dopamine in the molecular mechanisms of myopia.